PERAN ENGAGEMENT KERJA SEBAGAI MEDIATOR DALAM HUBUNGAN ANTARA PERSEPSI DUKUNGAN ATASAN DAN INTENSI TURNOVER - , mariana virdanianty ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main objective of this study is to explain the mediating role of work engagement in relation between perceived supervisory support and employee turnover intention. Based on work engagement model (Schaufeli & Bakker, 2004), the mediating role of work engagement was further examined in relation between supervisory support as job resources and employee turnover intention as work outcome. Supervisory support was assesed through subordinate perception concerning career dan development support from their immediate supervisor. Investigation was held for about two weeks with subjects are permanent employees in PT. X (n = 119). Result of path analysis revealed that work engagement was a fully mediator in relation between perceived supervisory support and employee turnover intention. Overall, this finding suggested that both perceived supervisory support and work engagement were important predictors that together with work engagement as mediator may more influence turnover intention than either predictor by itself or without work engagement as mediator. Implications for effective employee development management were also given.